The political ecology of hydropower in the Mekong River Basin - Geheb, Kim; Suhardiman, Diana (Elsevier, 2019)
Hydropower development in the Mekong River Basin is occurring at a rapid, though controversial pace, pitting a variety of stakeholder groups against each other at both intranational scale and international scale, and affecting state relations across scales. In this paper, we explore the narratives surrounding hydropower development in this basin, while referring to the concept of hydrosocial cycles as the central tool in our analysis. These look at the processes of socio-political construction of nature, viewing water as a medium that conveys power, and thus sources of both collaboration and conflict. While the Mekong hydropower narratives do, indeed, attempt to conflate the massive regulation of hydrological systems with large-scale social and economic ambitions, they are also intended to obscure a widespread and systemic effort to control and alienate the region’s waters via engineering at multiple scales.